ANALISIS KONTRIBUSI PAJAK BUMI DAN BANGUNAN (PBB) DAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) TERHADAP PENDAPATAN ASLI DAERAH DI KOTA PONTIANAK (STUDI KASUS PADA DISPENDA KOTA PONTIANAK - admin, Cindy B41112001 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This research aims to determine the contribution of land and building tax (PBB) and duty on land and building right acquisition (BPHTB) to the local own-source revenue of Pontianak period 2012-2015. Data sources of this research was obtained from interview (pimary data) and realization of the target data and report of local tax from 2012–2015 in Pontianak (secondary data). This study used a quantitative approach and the method of data analysis that used is descriptive. The result showed that (1) land and building tax give very low contribution to local own-source revenue with its average percentage is 9.07%. (2) duty on land and building right acquisition give low contribution to local own-source revenue with its average percentage is 32.02%.   Keywords:  Local  Tax,  Land  and Building  Tax (PBB),  Duty on Land  and Building Right Acquisition (BPHTB), Local Own-Source Revenue, Contribution.